2015
DOI: 10.1016/j.jpeds.2015.07.053
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Cardiometabolic Risk Factors between Parents and Children

Abstract: Objectives To explore the relations of parent-child cardiometabolic risk factors and assess the influence of adiposity on these associations. Study design Associations of adiposity, blood pressure, lipids, fasting insulin and glucose, and a risk factor cluster score were evaluated in a cross-sectional study of 179 parents and their children (6–18 years, N=255). Insulin resistance was assessed by euglycemic clamp in parents and children aged 10 or older. Metabolic syndrome in parents was defined by ATPIII cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…A large familial resemblance in metabolite concentrations has been suggested, which seems to be largely genetic (Draisma et al 2013;Kettunen et al 2016;Rueedi et al 2014). In cross-sectional studies, correlations of metabolites between parents and their offspring vary strongly, ranging from weak to relatively strong (Ellul et al 2019;Halvorsen et al 2015;Ohlund et al 2011). Partly in line with these previous studies, we observed that AA and NEFA concentrations were lower in childhood as compared to cord blood samples, whereas concentrations of PL and Carn were higher in childhood.…”
Section: Interpretation Of Main Findingssupporting
confidence: 90%
“…A large familial resemblance in metabolite concentrations has been suggested, which seems to be largely genetic (Draisma et al 2013;Kettunen et al 2016;Rueedi et al 2014). In cross-sectional studies, correlations of metabolites between parents and their offspring vary strongly, ranging from weak to relatively strong (Ellul et al 2019;Halvorsen et al 2015;Ohlund et al 2011). Partly in line with these previous studies, we observed that AA and NEFA concentrations were lower in childhood as compared to cord blood samples, whereas concentrations of PL and Carn were higher in childhood.…”
Section: Interpretation Of Main Findingssupporting
confidence: 90%
“…The pediatric and adult controls were obtained from prior studies of insulin resistance and cardiovascular risk at the University of Minnesota that utilized identical carotid imaging protocols [29,30,31,32]. Clinical data (demographic information, anthropometrics, ethnicity, confirmation of diagnosis, and treatment status) from MPS patients were obtained from chart review.…”
Section: Methodsmentioning
confidence: 99%
“…Parent–child dyad studies have suggested that obesity and certain cardiometabolic risk factors are shared across generations [ 9 , 10 , 11 ]. A study investigating longitudinal cardiovascular risk found that obese children with an obese parent were 21.2% likely to be eligible for bariatric surgery in adulthood [ 12 ].…”
Section: Introductionmentioning
confidence: 99%